Analisis Kesulitan Pemahaman Konsep Bangun Ruang Sisi Datar Ditinjau Dari Keterampilan Metakognisi Kelas VIII A SMPN 3 Narmada Tahun Ajaran 2020/2021 - Ridha Wahidatul Ilmi; Nyoman Sridana; Ulfa lu’luilmaknun; Amrullah Amrullah (Pendidikan Matematika FKIP Universitas Mataram, 2022)
The formulation of the problem in this research is to find out how difficult it is to understand students' concepts in the material of flat-sided geometry in terms of metacognition skills in class VIII A students of SMPN 3 Narmada for the 2020/2021 academic year. This study aims to describe the difficulty of understanding concepts in the flat-sided geometrical material in terms of the metacognitive skills of class VIII A students for the 2020/2021 academic year. This research uses descriptive qualitative research. The subjects of this study were students of class VIII A as many as 33 students. Data collection in this study was carried out using research instruments in the form of questionnaires, tests, and interviews. The results showed that students with high metacognitive skill category could fulfill all indicators of concept understanding. Students who have moderate metacognition skills can only fulfill two indicators of concept understanding, namely restating a concept, and applying the concept algorithmically. And students who have low metacognitive skills are only able to fulfill one indicator.